Multiplicity of EGFR and KRAS mutations in non-small cell lung cancer (NSCLC) patients treated with tyrosine kinase inhibitors - Benesova, Lucie; Minarik, Marek; Jancarikova, Dana; Belsanova, Barbora; Pesek, Milos (Anticancer research, 2010)
BACKGROUND: Concurrent presence of EGFR and KRAS mutations in non-small cell lung cancer (NSCLC) patients is relatively rare and their appearance is believed to be mutually exclusive. Tumours harbouring KRAS mutation are perceived as not being capable of response to tyrosine kinase inhibitor (TKI) therapy. PATIENTS AND METHODS: This paper presents 5 case reports of patients with tumours harbouring multiple EGFR and/or KRAS mutations. There were 3 patients with EGFR mutations (2 x exon 19 deletions, 1 x L858R) combined with KRAS mutations (2 x Gly12Asp, 1 x Gly12Val), 1 patient with two EGFR mutations (exon 19 deletion + L858R) and 1 patient with two KRAS mutations (Ala11Pro + Gly12Val). RESULTS: All EGFR(+)/KRAS(+) patients had initially showed positive response to TKI treatment. The EGFR(+)/EGFR(+) patient has exhibited strong rash and good response with the best survival, while the KRAS(+)/KRAS(+) patient did not respond to TKI therapy. CONCLUSION: EGFR(+)/KRAS(+) combination does not necessarily pose a negative prediction. This is probably due to the multiclonal character of the tumour displaying partial response in the EGFR(+) subpopulation.
Keywords: Genes, ras; Ras proteiny; senioři; Male; Female; Lung Neoplasms; ras Proteins; prognóza; Aged; Middle Aged; Protein-Tyrosine Kinases; tyrosinkinasy; ErbB Receptors; inhibitory proteinkinas; Models, Genetic; Prognosis; geny ras; mužské pohlaví; Mutation; ženské pohlaví; erbB receptory; nádory plic; Protein Kinase Inhibitors; lidé středního věku; Carcinoma, Non-Small-Cell Lung; lidé; modely genetické; Humans; mutace; nemalobuněčný karcinom plic